TINJAUAN HUKUM ISLAM TERHADAP UTANG PIUTANG DENGAN SISTEM NGAMBAK DI DUKUH BURAN KELURAHAN BABAT JERAWAT KECAMATAN PAKAL KOTA SURABAYA - Rista Fatimah (Maliyah : Jurnal Hukum Bisnis Islam, 2016)
This thesis is the result of field research on Islamic Law Review Against Debt With Ngambak System in the village of Buran Babat Jerawat Pakal Surabaya. This study was aimed to answer the questions: 1. How is the practice of debts with Buran system ngambak in Hamlet Village Subdistrict Pakal Babat Jerawat Surabaya? 2. How Islamic legal review of the debts with Buran system ngambak in Hamlet Village Subdistrict Pakal Babat jerawat Surabaya?. Results of this study concluded that the debts with Buran system ngambak in Hamlet Village Subdistrict Pakal Babat Jerawat Surabaya, in the view of Islam is legitimate and should be done because it has met the pillars and the terms of debts and do both sides with consensual (antaradin). Regarding the difference in the return of the debt, not including the additional prohibited under Islamic law. Due to the excess is merely a form of gratitude debtor to the creditor on loans given and when the contract is not mentioned nominal amount. But with an extra 5% or 10% as required pengambak fish to fish farmers at the time of the contract, if he could not give the fish at maturity (harvest). Then it is not in accordance with Islamic law, since the category of usury.